Sistem Pendukung Keputusan Penerima Bantuan Pangan Non Tunai (BPNT) Menggunakan Metode SMART - Wirnama, Moh. Izhar; Fahmi, Hairul; Bagye, Wire (Journal of Information System Research (JOSH), 2025)
The Non-Cash Food Assistance Program (BPNT) is one of the government’s social policies aimed at improving food security for low-income households. However, the beneficiary selection process in the field is often carried out manually and subjectively, which may lead to mistargeting. This study develops a Decision Support System (DSS) model based on the Simple Multi Attribute Rating Technique (SMART) to assist village officials in objectively determining the eligibility of prospective BPNT recipients, particularly in areas not yet supported by digital technology. The assessment was conducted using five main criteria, namely income, employment status, number of dependents, housing condition, and asset ownership. Eligibility determination was carried out by setting an average threshold value (≥ 0.305), where candidates with a final score equal to or above the threshold were categorized as eligible, while those below it were deemed ineligible. The analysis results showed that out of 11 prospective recipients, four candidates with scores of A4 = 0.925, A9 = 0.900, A5 = 0.700, and A1 = 0.450 were declared eligible to receive BPNT, while the remaining seven were deemed ineligible. The application of the SMART method has proven effective in improving transparency, objectivity, and proportionality in the selection process, making it a practical guideline for village governments or social service agencies in distributing aid fairly and accurately. In the future, this manual model can be integrated into web-based or mobile applications to enhance efficiency, accuracy, and data documentation, accompanied by regular evaluations to ensure that the criteria remain relevant to the socioeconomic dynamics of the community.